Artefact Festival : kunst en nieuwe media in Vlaams-Brabant. - STUK Kunstencentrum, Leuven (Leuven : STUK Kunstencentrum Leuven, 2007)
Asselberghs, Herman ; Beloff, Zoe ; Blonk, Jaap ; Campbell, Jim ; Cosic, Vuk ; Girardet, Christoph ; Janssen, Wim ; Kossakovsky, Victor ; Leroux, Brice ; Levin, Golan ; Lozano-Hemmer, Rafael ; Malstaf, Lawrence ; Meuris, Wesley ; Monolake ; Müller, Matthias ; Renz, Arco ; Schipper, Jonathan ; Simon, John F. Jr. ; Snow, Michael ; Taylor-Wood, Sam ; van Tellingen, Maurice ; Workspace-Unlimited
Nederlands
Exhibition. Artefactfestival. STUK Kunstencentrum Leuven, 13.02.2007 - 18.02.2007
boek